2010
DOI: 10.5194/hess-14-783-2010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on freshwater ecosystems: a global-scale analysis of ecologically relevant river flow alterations

Abstract: Abstract. River flow regimes, including long-term average flows, seasonality, low flows, high flows and other types of flow variability, play an important role for freshwater ecosystems. Thus, climate change affects freshwater ecosystems not only by increased temperatures but also by altered river flow regimes. However, with one exception, transferable quantitative relations between flow alterations and ecological responses have not yet been derived. While discharge decreases are generally considered to be det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
148
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(151 citation statements)
references
References 30 publications
3
148
0
Order By: Relevance
“…These conditions associated with increased evapotranspiration, might reduce the extent of flooded areas or convert them into drylands (Burkett and Kusler, 2000). The absence of an adequate period of flooding, in magnitude, duration and time, might cause a decline of many species which depend on flooding to complete their life cycle, and, in addition, might promote the establishment of invasive species (Poff, 2002;Döll and Zhang, 2010).…”
Section: The Reduced In Rainfall Scenariomentioning
confidence: 99%
“…These conditions associated with increased evapotranspiration, might reduce the extent of flooded areas or convert them into drylands (Burkett and Kusler, 2000). The absence of an adequate period of flooding, in magnitude, duration and time, might cause a decline of many species which depend on flooding to complete their life cycle, and, in addition, might promote the establishment of invasive species (Poff, 2002;Döll and Zhang, 2010).…”
Section: The Reduced In Rainfall Scenariomentioning
confidence: 99%
“…maximum and minimum water levels) are of increasing global attention because of the increased risk of floods and droughts on local or regional scales, as well as an increasing or decreasing water resources at the continental scale that have been observed Doell and Zhang, 2010;Assani et al, 2014). Meanwhile, water levels also have an important impact on the critical functions of river basins, such as ecosystem stability, water environment and engineering construction (Wen et al, 2011;Reid et al, 2013).…”
mentioning
confidence: 99%
“…Consequently, under the smallest climatic change scenarios, 18 % of species were found to be committed to extinction, while the largest change scenario projected as many as 35 % of species to be at risk (Thomas et al, 2004). Many studies investigated the impact of the streamflow change on the freshwater ecosystems, which will probably have strong effects on the system components and abiotic characteristics (Poff and Ward, 1989;Poff and Zimmerman, 2010;Döll and Zhang, 2010;Mantyka-pringle et al, 2012). Erwin (2009) concluded that the wetlands will strongly be influenced due to climate alteration and, to overcome all these impacts, assessment of the affect should first be conducted.…”
Section: Introductionmentioning
confidence: 99%